Decision on The Translation of Mandarin Song Lyrics 你要的爱 Into Indonesian by Yuni Shara in André Lefevere’s Perspective - Yogi Bagus Adhimas; Dhani Kristiandri; Fajar Sidiq Baehaqqi (Sinolingua: Journal of Chinese Studies, 2023)
This study discusses how the process of translating literary works of Mandarin song lyrics into Indonesian. In the translation process there are many things that influence, from the meaning of the word itself, to the purpose of the translation. This study aims to determine the translation method in the case study of the song "你要的爱" from Penny Tai which has been translated into Indonesian namely Yuni Shara's song entitled "Love that I Want", through André Levefere's point of view. By using qualitative research methods, the analysis of translation strategy assumptions is tried to be interpreted in depth and comprehensively. One result is that very few lyrics are translated integrally. More just take the core meaning and then change it to better consider the beauty of the musicality of the song in the target language.